2019
DOI: 10.3390/min9050299
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Classification of Opal with Reference to Recent New Localities

Abstract: Our examination of over 230 worldwide opal samples shows that X-ray diffraction (XRD) remains the best primary method for delineation and classification of opal-A, opal-CT and opal-C, though we found that mid-range infra-red spectroscopy provides an acceptable alternative. Raman, infra-red and nuclear magnetic resonance spectroscopy may also provide additional information to assist in classification and provenance. The corpus of results indicated that the opal-CT group covers a range of structural states and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(84 citation statements)
references
References 55 publications
10
74
0
Order By: Relevance
“…Wilson explained the opal-CT structure by a tridymite-dominant paracrystalline model [3]. Recent work by Curtis et al [4] found that opal-CT appears to be a paracrystalline form of silica that has some structural characteristics of cristobalite and tridymite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilson explained the opal-CT structure by a tridymite-dominant paracrystalline model [3]. Recent work by Curtis et al [4] found that opal-CT appears to be a paracrystalline form of silica that has some structural characteristics of cristobalite and tridymite.…”
Section: Introductionmentioning
confidence: 99%
“…Other techniques, such as infrared spectroscopy [5][6][7] and Raman spectroscopy [8][9][10][11][12][13][14], have also been used to distinguish different types of opal. Furthermore, Raman spectroscopy has been considered a method to distinguish the complex structural relationships between different types of opal [4,8,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…X-ray powder diffraction data were obtained using powder diffractometer working with graphite monocromatized Cu Kα radiation in the range 2θ, 10-70°. The X-ray powder diffraction analyses performed are able to classify opals in to their common groups such as opal-A, opal-C and opal-CT [25,29]. XRD patterns for natural and heat treated opals are shown in (Fig.…”
Section: Xrd Determinationmentioning
confidence: 99%
“…The common methods for determining phosphorite grade include conventional chemical analyses, infrared spectroscopy, nuclear magnetic resonance, X-ray spectroscopy, and plasma mass spectrometry, etc. [5][6][7][8][9][10], however, most of these methods require complex sample preparation and are difficult to perform on site for underground measurements. Therefore, it is of great interest to study a powerful method to meet these difficulties.…”
Section: Introductionmentioning
confidence: 99%